A novel cross-linked PVA-Chitosan composite membrane for heavy metal filtration applications. (2022) - Deekshitha, K.; Rao, Mahima S; Rebello, Nalini; Ramaprasad, A.T; Jayarama, A.; Pinto, Richard
Abstract: A novel glutaraldehyde cross-linked Chitosan-PVA (GCP) polymer composite membrane is used to create a water filtration device. The GCP polymer membrane is synthesised using the solution casting process. GCP membranes are characterised using different techniques. The results showed that this filtration unit developed using GCP membrane is effective in reducing the Lead, Cadmium, Sodium and Iron content by 99.32%, 98.1, 88.21% and 78.9% respectively. The creation of nano-pores in GCP membrane, the adsorbent property of GCP and the thermal and chemical stability of GCP are the key factors leading to high performance filtration of major metal contaminants in ground water.